Sistem Informasi Lulusan Dengan Metode Online Analitycal processing (OLAP) Pada Politeknik Negeri Kupang - Ndoloe, Lita Alfriany (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
The  educational  institution  need  the  leadership/  decision  makers  are  always  trying  to  find  some  information  /  decisions  that  are beneficial to the students, so that when they graduate can get a job quickly. To make it easier to get the information using OLAP. The purpose  of this research  is  to  make  information  systems  graduates  by using  Online Analytical  Procesing  (OLAP).  In the  modelingsystem  used  Context  Diagram  and  Data  Flow  Diagram.  Information  systems  graduates  begins  with  collecting  data  on  graduates, perform  analysis  with  the  concept  of  Roll  Up,  presents  information  generated  OLAP  and  graphs.  Graduate  information  systemsprovide  information  quality  graduates,  useful  for leaders  to make decisions.  Graduate  information  systems  can be  applied to the State Polytechnic  Department of Electronics  Kupang.  Results  showed  developmental  process  OLAP  uptake  needs  graduates  in  public and private.Keywords: OLAP,Graduate  information systems, Roll Up